2010
DOI: 10.1080/00222895.2010.504759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auditory Feedback on Movement Time in a Fitts Task

Abstract: The purpose of the present experiment was to investigate the role of auditory feedback and its impact on movement time in a standard Fitts task. Feedback was given at the moment of target acquisition. A 2-way analysis of variance found significant differences between feedback groups at all three indexes of difficulty (F(2, 40) = 156.02, p < .001). Results from a mixed-model multivariate analysis of variance for kinematic factors show significant differences in peak velocity and the location of peak velocity wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The shorter average MT observed in the presence of augmented spatial terminal feedback was hypothesized and has been previously reported (i.e., Hatfield et al, 2010). Indeed, Hatfield et al (2010) observed that more recent incarnations of Fitts' reaching paradigm (e.g., displacing a cursor on a screen) do not provide much feedback about endpoint accuracy.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…The shorter average MT observed in the presence of augmented spatial terminal feedback was hypothesized and has been previously reported (i.e., Hatfield et al, 2010). Indeed, Hatfield et al (2010) observed that more recent incarnations of Fitts' reaching paradigm (e.g., displacing a cursor on a screen) do not provide much feedback about endpoint accuracy.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, Hatfield et al (2010) observed that more recent incarnations of Fitts' reaching paradigm (e.g., displacing a cursor on a screen) do not provide much feedback about endpoint accuracy. To test the importance of spatial terminal feedback, they asked participants to complete reciprocal reaching movements with a cursor to 3 pairs of targets of differing IDs (4.03, 5.07, and 7.64 bits).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations